Planteamiento de una narrativa gráfica sobre las interacciones de las identidades de los estudiantes de la Universidad Autónoma de Occidente - Cali 2017. (2018)
The Life’s Stories have always been the basis of the documentation of success and experiences, from them it`s generated a series of analytical, methodological and practical processes by which the people search from them for find the solution to a particular problem. The university amass a diversity of stories, known as metanarratives, from that point the graduation project part by an approach of the identity interactions of the students of the University of Autónoma de Occidente in Cali, Colombia; through a graphic narrative, supported in the format of Comic with the method of the autobiographical narrative or Life writing and without forget, the hermeneutic exercise of the lecture and interpretation of the supported information